Characterization of Aluminum-Substituted Yttrium-Iron Garnet Nanoparticles Prepared Using the Sol-Gel Technique - Al-Habashi, Ramadan Masoud (2006)
This project presents preparation and characterization of aluminum substituted yttrium iron garnet (Al-YIG) nanocrystalline powders of compositional variation of Y3.0-xAlxFe5O12, where x was 0, 0.5, 1, 1.5, 2, 2.5 and 3. The samples were synthesized using sol–gel technique. The starting raw materials used to prepare Al-YIG samples were aluminum nitrate (Al(NO3)3.9H2O), yttrium nitrate (Y(NO3)3.6H2O) and iron nitrate (Fe(NO3)3.9H2O). They were weighed according to the formula above, then mixed and dissolved together in solution of citric acid (C6H8O7.H2O) for a month to form the gel form by using magnetic stirrer equipment at 350 r.p.m at room temperature. The sample was then dried at 110oC in an oven for a day to remove the unneeded water before it was calcined and crushed to obtain fine particles powder. The calcined powder at 600oC, 700oC, 800oC, 850oC and 900oC respectively, were characterized by x-ray diffraction analyzer (XRD) to confirm the garnet phase. All samples were characterized also by RF-Impedance (1 MHz-1.8 GHz) to investigate the magnetic properties. Finally, field emission scanning electron microscopy (FESEM) and energy dispersive x-ray analyzer (EDX) were used to study the surface morphology and the elemental analysis of Al-YIG samples. The results showed that, the best garnet phase appeared when the sintering temperature was 800oC and Al-YIG nano-crystalline samples with high purity and sizes ranging from 20 to 100 nm were obtained. The magnetic measurement results of Al-YIG samples prepared by sol-gel method, gave high values of real permeability, the highest value of 5.29 was given by Y3Fe5O12 sample at about 80 MHz which was attributed to the large grain size, the highest magnetic permeability observed was due to easy movement of domain walls; and it shifted to the high frequency with increasing the amount of aluminum. The widest useful working frequency range appeared for Y3Fe5O12 sample and, also shifted to reach high range with increasing the concentration of aluminum.